Amino Acid Intakes Are Inversely Associated with Arterial Stiffness and Central Blood Pressure in Women. Issue 9 (22nd July 2015) - Jennings, Amy; MacGregor, Alex; Welch, Ailsa; Chowienczyk, Phil; Spector, Tim; Cassidy, Aedín
Abstract: Background: Although data suggest that intakes of total protein and specific amino acids (AAs) reduce blood pressure, data on other cardiovascular disease risk factors are limited. Objective: We examined associations between intakes of AAs with known mechanistic links to cardiovascular health and direct measures of arterial stiffness, central blood pressure, and atherosclerosis. Methods: In a cross-sectional study of 1898 female twins aged 18–75 y from the TwinsUK registry, intakes of 7 cardioprotective AAs (arginine, cysteine, glutamic acid, glycine, histidine, leucine, and tyrosine) were calculated from food-frequency questionnaires. Direct measures of arterial stiffness and atherosclerosis included central systolic blood pressure (cSBP), mean arterial pressure (MAP), augmentation index (AI), pulse wave velocity (PWV), and intima–media thickness (IMT). ANCOVA was used to assess the associations between endpoints of arterial stiffness and intake (per quintile), adjusting for potential confounders. Results: In multivariable analyses, higher intakes of total protein and 7 potentially cardioprotective AAs were associated with lower cSBP, MAP, and PWV. Higher intakes of glutamic acid, leucine, and tyrosine were most strongly associated with PWV, with respective differences of −0.4 ± 0.2 m/s ( P -trend = 0.02), −0.4 ± 0.2 m/s ( P -trend = 0.03), and −0.4 ± 0.2 m/s ( P -trend = 0.03), comparing extreme quintiles. There was a significant interaction between AA intakes and protein source, and higher intakes of AAs from vegetable sources were associated with lower central blood pressure and AI. Higher intakes of glutamic acid, leucine, and tyrosine from animal sources were associated with lower PWV. Conclusions: These data provide evidence to suggest that intakes of several AAs are associated with cardiovascular benefits beyond blood pressure reduction in healthy women. The magnitude of the observed associations was similar to those previously reported for other lifestyle factors. Increasing intakes of these AAs could be an important and readily achievable way to reduce cardiovascular disease risk.